Creencia en la benevolencia humana en delincuentes: un estudio inicial en función al delito - Díaz Huamán, Susana V. (1989)
Thomton and Kline (1982) Belief in Human Benevolence Scale is used to assess 60 subjects confined in a Penitentiary Institution. The main goal was to stablish if belief in human benevolence varies according to the type of transgression, juridical condition, time of confinement, age and instruction. Statistical results with t-student and r-Pearson show that prisoners that have not yet been jugded, that have less time in the institution and that are older and with higher instruccional level show a higher mistrust in human benevolence. Results are discussed.